Bản tổng hợp thảo luận tại Hội trường (Ghi theo băng ghi âm) Buổi chiều ngày 08/11/2021 - Quốc hội (2021)
Toàn văn Bản tổng hợp thảo luận tại Hội trường (Ghi theo băng ghi âm) Buổi chiều ngày 08/11/2021